(untitled) (Papeles, 2022)
The formulation of international legal cooperation has evolved, it is no longer simply a matter of mere cooperation or reciprocity, efforts are aimed at generating mechanisms to facilitate judicial work and collaboration between judicial bodies for the collection of evidence, the conduct of proceedings, the adoption of specific measures, the aim is to eliminate the reduction of requirements for exequatur and even its elimination, for hindering the recognition and enforceability of judicial decisions and sentences, in order to build spaces of legal certainty and to facilitate and achieve justice beyond borders.